2020
DOI: 10.1111/jors.12478
|View full text |Cite
|
Sign up to set email alerts
|

The geography of unsheltered homelessness in the city: Evidence from “311” calls in New York

Abstract: We provide the first detailed evidence on the distribution of unsheltered homelessness within the city. We rely on “311” call data reporting unsheltered homeless individuals to New York City authorities, based on evidence that the distribution of calls reflects their actual locations. Centrality dominates an otherwise important role of median income in explaining variation in unsheltered homelessness across neighborhoods. Subway stations and restaurants are important as well. We also find that police respond m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The results indicate that unsheltered homeless people in the study area are heavily concentrated in and around the city center and in neighborhoods with greater access to shelters and with lower socioeconomic status. Unlike in New York (Corinth and Finley 2020), poverty rates are positively associated with unsheltered homeless population density in the Los Angeles area. Notably, neighborhoods closer to the city center experienced a relatively large increase in unsheltered homelessness during the study period, implying a persistent spatial concentration of unsheltered homelessness.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…The results indicate that unsheltered homeless people in the study area are heavily concentrated in and around the city center and in neighborhoods with greater access to shelters and with lower socioeconomic status. Unlike in New York (Corinth and Finley 2020), poverty rates are positively associated with unsheltered homeless population density in the Los Angeles area. Notably, neighborhoods closer to the city center experienced a relatively large increase in unsheltered homelessness during the study period, implying a persistent spatial concentration of unsheltered homelessness.…”
Section: Introductionmentioning
confidence: 82%
“…Some urban parks serve as refuges, partly due to their shower facilities and bathrooms. Corinth and Finley (2020) revealed that subway stations also significantly explain neighborhood variations in unsheltered homelessness.…”
Section: Literature Review and Backgroundmentioning
confidence: 97%
See 3 more Smart Citations